Qualidade de vida de cuidadores de paciente com câncer terminal - Teles, Antônio Gomes (2014)
When concerning quality of life (QOL), several issues must be considered, due to the complexity of the way people face life, their behave and feelings, including health status.In this scenery the QOL of caregivers should be aimed, specialy of those who give domiciliary assistance to terminal cancer patients. The objective of the presente study was to evaluate the QOL of terminal cancer domiciliary caregivers entitled GAPPO (Support Paliative Oncological Group), in the metropolitan área of Goiania/Goias/Brazil.This was a correlational, descriptive, transversal stydy, developed with patients of the Hospital Araujo Jorge of the Association Agaisnt Cancer of Goias (ACCG). The WHOQOL– BREF (portuguese version) query was applied, individually, during patients domiciliar visits to access each caregiver.Microsoft ® Excel 2007 was used for data tabulation and statistical analysis was developed in SPSS® for Windows®, version 16.0. The social-demographics profile was considered in WHOQOL – BREF query and analised with t-Studenttest, using ANOVA (Tukey test) for normal distribution.Chi-square test was also used for univariate social-demographic analysis. Correlation analysis was performed with Pearson test, considering significance with a p value < 0.05 for all tests. Fourty three domiciliary caregivers were included, all indicated by the patients seen. 79.1 % ofthecaregiverswerewomen, 65.1% married. Around 51% of the sample were over 50’s, 39.5% caucasians, 55.8% completed college and 67.4% were catholics. The time of professional activity may increase psych emotional distress. Around 60% of the caregivers had less than one year of experience, 41.8% with 24h daily duty and almost 98% of all with non-profit activity. The amount of daily working hours has impacted fisical and psychologically the caregivers. The highest negative QOL impact was seen in the psych field, witha mean of 52.8 for those working up to 5 hours a day, although reaching 68.5 for caregivers working 6 to 11 hours a day. The results showed that the patient´s income variable results in worse QOL of the caregivers, once it is associated to a higher risk of severe pain, need of medical assistance, mobility problems, costs with energy and even ability to develop daily activities. The results of correlation of WHOQOL-BREF query variables showed mild to high significance. The work developed by the caregivers with this kind of patients lead to a poor QOL. The conclusions of the present work suggest that caregivers themselves need care in order to preserve their QOL.